2011
DOI: 10.1002/crat.201100344
|View full text |Cite
|
Sign up to set email alerts
|

Effect of copper (II) ion against elongation behavior of amyloid β fibrils on liposome membranes

Abstract: The fibril growth behavior of amyloid β protein (Aβ) on cell membranes is relating to the progression of Alzheimer's disease. This growth behavior of Aβ fibrils is sensitively affected by the metal ions, neurotransmitters, or bioreactive substrate. The inhibitory effect of those materials was quantitatively estimated from the viewpoints of "crystal growth". In a bulk aqueous solution, copper (II) ion showed the strong inhibitory effect on the growth of Aβ fibrils. Meanwhile, the addition of a closed-phospholip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…I) Initial period is characterized by no obvious change of resistance during the first 8 h. The result indicates that little interaction occurs between Aβ(1–40) and the PC membranes. Accumulating evidences show that monomeric Aβ is nontoxic and hardly interacts with PC membranes at neutral pH . It may be because the interactions between Aβ and membranes with zwitterionic lipid surfaces are mainly dominated by hydrophobic interactions as mentioned in the section of introduction, however Aβ monomers have little hydrophobicity to interact with the membranes .…”
Section: Resultsmentioning
confidence: 99%
“…I) Initial period is characterized by no obvious change of resistance during the first 8 h. The result indicates that little interaction occurs between Aβ(1–40) and the PC membranes. Accumulating evidences show that monomeric Aβ is nontoxic and hardly interacts with PC membranes at neutral pH . It may be because the interactions between Aβ and membranes with zwitterionic lipid surfaces are mainly dominated by hydrophobic interactions as mentioned in the section of introduction, however Aβ monomers have little hydrophobicity to interact with the membranes .…”
Section: Resultsmentioning
confidence: 99%
“…The authors observed the ability of Cu 2+ to inhibit the fibrils’ growth in a bulk aqueous solution. However, the presence of the membrane model attenuated this inhibitory effect [51] . Specifically, they found that Cu 2+ inhibits the nucleation phase, leading to the formation of Aβ/Cu complexes, which are inactive to the fibrils’ growth.…”
Section: Factors Modulating Aβ‐lipid Membrane Interactionsmentioning
confidence: 99%
“…Shimanouchi et al . (2011) [50–51] investigated the copper (Cu 2+ )‐mediated growth of Aβ 1–40 fibrils in absence and presence of oxidized and negatively charged LUVs. The authors observed the ability of Cu 2+ to inhibit the fibrils’ growth in a bulk aqueous solution.…”
Section: Factors Modulating Aβ‐lipid Membrane Interactionsmentioning
confidence: 99%
“…Subsequently, Shimanouchi and co-workers first observed the growth behavior of Aβ fibrils in the presence of liposomes and metal ion (copper­(II) ion). The influences of those additives on the growth behavior of amyloid fibrils were also quantitatively investigated to estimate the inhibitory effect . The result of this work indicated that copper­(II) ion showed the strong inhibitory effect on the growth of Aβ fibrils in a bulk aqueous solution.…”
Section: Experimental Research Progressmentioning
confidence: 99%
“…The influences of those additives on the growth behavior of amyloid fibrils were also quantitatively investigated to estimate the inhibitory effect. 38 The result of this work indicated that copper(II) ion showed the strong inhibitory effect on the growth of Aβ fibrils in a bulk aqueous solution. Successively, Lovas and co-workers combined AFM and Molecular Dynamics (MD) simulations for characterizing the misfolding process of an Aβ peptide.…”
Section: Experimental Research Progressmentioning
confidence: 99%